RANCANG BANGUN SISTEM INFORMASI POINT OF SALE MULTI OUTLET DENGAN MENGGUNAKAN FRAMEWORK LARAVEL DI KOPERASI ITSNU PEKALONGAN - Abdul Razak Naufal (Politeknik Bisnis Indonesia, 2022)
Digitalization has been shaped the economy and society, one of the areas most affected by digitalization is the retail sector. Point Of Sale (POS) is a sales-oriented activity and a system that helps process transactions. The Cooperative store at the Technology and Science Institute of Nahdlatul Ulama (ITSNU) Pekalongan still records manually, so there is a risk of fraud and data loss. This POS system can be helping all transactions to manage stores to be fast, accurate and safe, because all of data will be saved to the cloud directly, so cooperative managers can be controlling several cooperatives directly, anytime and anywhere. The method used in this POS system is the Waterfall method, which is a method used to develop software sequentially like a waterfall through several stages are data collection, analysis, design, development, testing and implementation. Based on the black box testing that the researchers have done, all the features on this multi-outlet POS system have functioned properly according to the needs of cooperatives at ITSNU Pekalongan.